Antimicrobial peptides in frog poisons constitute a molecular toxin delivery system against predators. Issue 1 (December 2017) - Raaymakers, Constantijn; Verbrugghe, Elin; Hernot, Sophie; Hellebuyck, Tom; Betti, Cecilia; Peleman, Cindy; Claeys, Myriam; Bert, Wim; Caveliers, Vicky; Ballet, Steven; Martel, An; Pasmans, Frank; et al.
Abstract Animals using toxic peptides and proteins for predation or defense typically depend on specialized morphological structures, like fangs, spines, or a stinger, for effective intoxication. Here we show that amphibian poisons instead incorporate their own molecular system for toxin delivery to attacking predators. Skin-secreted peptides, generally considered part of the amphibian immune system, permeabilize oral epithelial tissue and enable fast access of cosecreted toxins to the predator's bloodstream and organs. This absorption-enhancing system exists in at least three distantly related frog lineages and is likely to be a widespread adaptation, determining the outcome of predator–prey encounters in hundreds of species. To avoid being eaten, poisonous prey animals must rely on fast passage of toxins across a predator's oral tissue, a major barrier to large molecules. Here, Raaymakers et al. show that antimicrobial peptides co secreted with frog toxins enhance intoxication of a snake predator by permeabilizing oral cell layers.